Education mismatch among overseas Filipino workers - Basas, Rachelle Anne R. (School of Economics, University of the Philippines Diliman, 2018)
This study aims to determine whether and to what extent skills mismatch, particularly overeducation, exists among Overseas Filipino Workers (OFWs). It uses the OECD definition of overeducation, which is based on the correspondence between the ISCO1 occupational classifications and ISCED2 education classifications. Overeducation arises when the level of education of a worker exceeds the level required by his or her job. Using data from the Survey on Overseas Filipinos (SOF), the study finds that approximately half of the OFWs are overeducated. The destination country, occupation, and demographic variables, such as the marital status and household headship of an OFW influence his or her likelihood of becoming overeducated. Lastly, this paper reinforces the argument that mismatch, particularly overeducation, among OFWs is primarily rooted in the inefficiencies in the Philippine educational system.